Efeitos do bloqueio triplo experimental do sistema renina-angiotensina-aldosterona no desenvolvimento da nefropatia diabética - Costa, Emerson Nunes (2013)
The Diabetes Mellitus (DM) is a group of metabolic diseases, with hiperglycemia resulting from defects in insulin secretion (type 1 DM) and / or action (type 2 DM), promoting the elevation of blood glucose levels, which can damage target organs (eyes, kidneys, nerves, heart). In the kidney presents as diabetic nephropathy (DN), characterized by increased levels of urinary albumin excretion (UAE), which could progress to end stage kidney disease. The renin-angiotensin-aldosterone system (RAAS) is an important mediator of the pathophysiological changes of DN. The pharmacological blockade of this system has been shown as a combined treatment of DN, decreasing urinary albumin excretion. The aim of this study was to evaluate the effects of triple RAAS blockade on kidney structure and function, as well as albuminuria in diabetic Wistar rats with DN in development. Induction of diabetes in rats was performed with intravenous administration of alloxan (50mg/kg) diluted in 0.9% saline and glycemia observed 24h after the induction of diabetes; animals with blood glucose greater than 200 mg/dL were considered diabetic and were divide into 5 groups: I) control group - no treatment (CG); II) experimental group 1 - treated with enalapril (EN) (angiotensin converting enzyme inhibitor - ACEI), III) experimental group 2 - treated with losartan (LO) (angiotensin receptor blocker - ARB), IV) experimental group 3 - treated with aliskiren (AL) (direct renin inhibitor - DRI); V) experimental group 4 - treated with triple blockade ACEIARB- DRI (EN+LO+AL). After 90 days of treatment, animals were placed in metabolic cages to collect 24-hour urine and thereafter for determination of blood, proteinuria, and glomerular filtration rate by creatinine clearance. Then, the animals were anesthetized and had their kidneys removed for histological and immunohistochemical studies (α-SMA and PCNA). After induction, all animals that became diabetic, remained with high glycemic levels throughout the treatment period. Histology showed on CG glomerular collagen deposition and tubulointerstitial, tubular dilation, space capsule expansion and inflammatory infiltration; those changes were attenuated by treatments with EN, LO, AL and EN+LO+AL. The treatments reduced the expression of α-SMA glomerular (EN p<0.01; LO p<0.01; AL p<0.05, EN+LO+AL p<0.01) and tubulointerstitial (EN p<0.05, AL p<0.01, EN+LO+AL p<0.05) compared to CG. There were no significant differences in the number of PCNA glomeruli positive cells and in the analysis of plasma concentrations of sodium, potassium and urea between groups. However, EN and LO preserved a largest number of proliferating tubulointerstitial cells. Rats treated with AL (p<0.05) and EN+LO+AL (p<0.05) had a higher glomerular filtration rate (GFR) when compared to CG, EN and LO. AL and EN+LO+AL significantly reduced proteinuria in these animals when compared to CG (p<0.01). The treatment with EN+LO+AL reduced the expression of α-SMA glomerular and tubulointerstitial, preserved a greater number glomeruli, GRF and UAE. However, administration of AL resulted in similar data.